Novel Design of Eco-Friendly Super Elastomer Materials With Optimized Hard Segments Micro-Structure: Toward Next-Generation High-Performance Tires - Qin, Xuan; Wang, Jiadong; Han, Bingyong; Wang, Bo; Mao, Lixin; Zhang, Liqun (Frontiers in Chemistry, 2018)
Nowadays, sustainable development has become a significant concern all over the world, among which the energy crisis is the top priority. From the perspective of the industrial application of polymeric materials, rubber tires are critically important to our daily life. However, it should be pointed out that the energy consumption of tires can reach 6% of the world’s total energy consumption per annum. Meanwhile, it is calculated that around 5% of carbon dioxide comes from the emission of the tire rolling because of the energy consumption. To overcome these severe energy and environmental challenges, designing and developing a high-performance fuel-saving tire is of paramount significance. Herein, a next-generation, eco-friendly super elastomer material based on macromolecular assembly technology has been fabricated. Hydroxyl-terminated solution-polymerized styrene-butadiene rubber (HTSSBR) with high vinyl contents prepared by anionic polymerization is used as flexible soft segments to obtain excellent wet skid resistance. Furthermore, highly symmetrical 1,5-naphthalene diisocyanate (NDI), different proportions of chain extender and the cross-linking agent with moderate molecular length are selected as rigid hard segments with the purpose of achieving simultaneous high heat resistance. Through this approach, a homogeneous network supported by uniformly distributed hard segment nanoparticles is formed because soft segments with the equal length are chemically end-linked by the hard segments, and this super elastomer material exhibits excellent wear resistance and low rolling resistance remarkably. More importantly, the wear resistance, rolling resistance, and wet-skid resistance are reduced by 85.4%, 42.3%, and 20.8%, respectively, compared to the elastomeric material conventionally used for tire. By taking advantage of this excellent comprehensive service performance, the long-standing challenge of the "magic triangle" plaguing the rubber tire industry for almost hundred years is resolved. It is anticipated that this newly designed and fabricated elastomeric material tailored for tires will become the next generation product, which could exhibit high potential for significantly cutting the fuel consumption and reducing the emission of carbon dioxide.